2009
DOI: 10.1007/s00701-009-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation and facial nerve function after microsurgery for intracanalicular vestibular schwannomas: comparison of middle fossa and restrosigmoid approaches

Abstract: We believe that the timing of treatment in the course of the disease and selection between radiosurgical versus microsurgical procedure are key issues in the management of IVS. Preservation of hearing and good facial nerve function in surgery for VS is a reasonable goal for many patients with intracanalicular tumors and serviceable hearing. Once open surgery has been decided, selection of the approach mainly depends on individual anatomical considerations and experience of the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…59,81 The higher incidence of facial nerve dysfunction for all patients with tumors larger than 3.0 cm is likely related to the effect of tumor size. 17,26,42,65,66,77 In summary, our analysis demonstrates the clear benefit of the retrosigmoid approach specifically for facial function among patients with tumors that are intracanalicular and 1.5-3.0 cm in size, with no difference in benefit between the middle cranial fossa and retrosigmoid approaches for patients with extrameatal tumor diameters less than 1.5 cm. For most tumor sizes, the translabyrinthine approach seems to be associated with a higher rate of facial nerve dysfunction.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…59,81 The higher incidence of facial nerve dysfunction for all patients with tumors larger than 3.0 cm is likely related to the effect of tumor size. 17,26,42,65,66,77 In summary, our analysis demonstrates the clear benefit of the retrosigmoid approach specifically for facial function among patients with tumors that are intracanalicular and 1.5-3.0 cm in size, with no difference in benefit between the middle cranial fossa and retrosigmoid approaches for patients with extrameatal tumor diameters less than 1.5 cm. For most tumor sizes, the translabyrinthine approach seems to be associated with a higher rate of facial nerve dysfunction.…”
mentioning
confidence: 60%
“…Data for facial nerve dysfunction and hearing loss were stratified based on tumor size because tumor size has been shown to be the most important predictive factor for outcome related to these variables. 17,26,42,65,66,77 Tumors were stratified as entirely IC (no extrameatal extension) or based on their extrameatal diameter (< 1.5 cm, 1.5-3.0 cm, or > 3.0 cm into the CPA). Table 1 summarizes the results for different clinical variables based on surgical approach.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Class II or higher evidence for intracanalicular VS managed through microsurgery is lacking. Recently, Noudel et al 70 conducted a systematic review that included 35 studies of microsurgical resection of intracanalicular VS. They reported that the average hearing preservation rate (AAO-HNS Classes A and B or GRC I and II) for intracanalicular VS was 58% with a retrosigmoid approach and 62% with a middle fossa approach.…”
Section: Facial Nerve Outcomes After Microsurgerymentioning
confidence: 99%
“…The middle fossa approach and the retrosigmoid approach offer similar hearing preservation. 14) The advantage of the retrosigmoid approach is comfortable exposure of the tumor and adjacent dura, and good control of the neurovascular structure. 5) The relationship between the facial or cochlear nerve and the tumor is predictable for VSs, but the nerve bundle has a more variable relationship with meningiomas.…”
Section: Iac Meningioma With Rapidly Progressive Hearing Lossmentioning
confidence: 99%